Change in soccer substitutions rule due to COVID-19: Why only five substitutions? - Mota, G. R.; Aparecida Santos, I.; Marocolo, M. (Frontiers in Sports and Active Living, 2021)
Soccer has a high rate and percentage of injuries (Elias, 2001; Wong and Hong, 2005), and more injuries have been observed in soccer than in several other sports (Yde and Nielsen, 1990; Wong and Hong, 2005). Interestingly, the injury rate is markedly higher (~10 times) during matches than training sessions (López-Valenciano et al., 2020), due to several factors such as higher overall demands (e.g., number of contacts/collisions), higher fatigue (e.g., competing against opponents in matches instead of teammates in training) would potentiate these discrepancies (Ekstrand et al., 2011a,b; López-Valenciano et al., 2020). Additionally, the incidence of injuries increases toward the end of each half, indicating that fatigue is involved in injury etiology (López-Valenciano et al., 2020). In training sessions, coaches control the load (e.g., the number of sprints, duration of the session), but load management is much more difficult due to external factors and the nature of the match. Therefore, beyond all previous preparation of the players (e.g., training plan, nutrition, recovery strategies), it is reasonable to consider that "a better" match management (e.g., changes in the rules) might support injury prevention.